Perioperative Immunonutrition in Well-Nourished Patients Undergoing Surgery for Head and Neck Cancer: Evaluation of Inflammatory and Immunologic Outcomes - Turnock, Amy (MDPI, 2013)
Limited work is available on the benefits of nutritional support enriched with arginine and n-3 fatty acids in surgical patients with head and neck cancer, particularly if well-nourished. We conducted a pilot study in these patients to examine effects on inflammatory markers and clinical outcome. Patients scheduled for radical resection of the oral cavity were randomised to 5 day preoperative and 5 day postoperative Impact(®) (IMN, n = 4), or no preoperative supplementary nutrition and Isosource(®) postoperatively (STD, n = 4). Plasma fatty acids, C-reactive protein (CRP), tumour necrosis factor (TNF)-α, interleukin (IL)-6 and IL-10 were measured at baseline, day of surgery and on postoperative days (POD) 2, 4 and 10. Postoperative complications were recorded. The (eicosapentaenoic acid plus docosahexaenoic acid) to arachidonic acid ratio was significantly higher in IMN patients on POD 2, 4 and 10 (P < 0.01). While not statistically significant, CRP, TNF-α, and IL-6 concentrations were higher in the STD group on POD2 while IL-10 was lower. Median length of stay was 10 (range 10–43) days in the IMN group and 21.5 (7–24) days in the STD group. Five complications were seen in the STD group and two in the IMN group. The results support the need for a larger trial focusing on clinical outcome.